A formação estética no curso de gastronomia: a relevância da utilização de filmes nos procedimentos pedagógicos - Venâncio, Antonio (2010)
The objective of this work is to reflection the relevance of cinema in the professional and human training of students in the course of gastronomy. The work is developed by analyzing social and human phenomena, which is necessary for the aesthetical training in the Course of Gastronomy. In order to accomplish this study, theoretical references were searched: readings on education linked to the complexity of contemporary world; readings on cinema, an artistic phenomenon that can have didactic functions, therefore establishing its role as an educative and training phenomenon. Documental Analysis has been adopted as data collection and analysis method and procedure. Documents focused on the analysis of teacher training processes in contemporary world, and theoretical documents on the cinema seen as an artistic language, have been researched. There was a selection of films whose themes were adequate to the content of the Gastronomy Course, among them Ratatouille, which was subject to a deeper analysis in the work, by emphasizing the bonds between the themes of the film and the Course of Gastronomy. The study resulted in a perception of the existence of a close relationship between cinema and education. This relationship results from sensitivity training. The use of films leads gastronomy course students to think about the phenomena of reality. A careful analysis of films is important to perfect individuals, to train citizens, i.e., autonomous citizens. This practice aims at the “full development of the person”, by understanding that autonomy and authorship, as ethical values, relate to the formation of an integral human being